PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, INVESTMENT OPPORTUNITY SET, CAPITAL INTENSITY DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI - Yudi Partama Putra; Mela, Mela Tri Ramadannia; Yusmaniarti, Yusmaniarti; Ummul Khair (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the influence of managerial ownership, institutional ownership, investment opportunity set, capital intensity, and profitability on accounting conservatism in consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the 2018–2022 period. This study uses a quantitative approach with secondary data in the form of annual financial reports. The study population includes all consumer goods manufacturing companies listed on the IDX, with purposive sampling method used to select the sample, resulting in 28 companies, or 140 observations. Data analysis was performed using multiple linear regression with the aid of SPSS. The results indicate that managerial ownership, institutional ownership, investment opportunity set, capital intensity, and profitability simultaneously have a significant effect on accounting conservatism. However, partially, managerial ownership, institutional ownership, investment opportunity set, and capital intensity do not significantly influence accounting conservatism, while profitability has a positive and significant effect. These findings indicate that corporate profit levels are the primary factor driving the application of accounting conservatism principles, while ownership mechanisms and investment characteristics have not been able to optimally influence conservatism policies in financial reporting. Keywords: Accounting Conservatism, Managerial Ownership, Institutional Ownership, Investment Opportunity Set, Profitability